(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article reviews current definitions of environmental management: institutional, processual, system and functional; it’s offered to interpretate ecological management from the perspective of institutional and processual views. Under the institutional view, environmental management of the enterprise is a set of principles, forms, methods, techniques and tools of influence, which, on the one hand, used by the personnel to achieve high work performance, on the other – to provide safe ecological activity basing on rational and sustainable nature management that does not harm the environment. Elements of the environmental management of the enterprise (subject, object, a subject, the purposes, tasks, objectives, instruments, tools, methods, the expected results) are defined. According to the processual view, environmental management of the enterprise is a set of consecutive interconnected stages of administrative activity, which provides justification, adoption and implementation of management decisions for ecologically safe and cost-effective strategy of the ecological management of the enterprise, namely: formation of ecologically oriented conception of development of the enterprise; strategic analysis of the environment; diagnostic of the ecological and economical security of the enterprise; forecasting of changes in the strategic environment of the enterprise; ecologically purpose-setting; justification of a strategic plan of development of the enterprise; development of ecological policy; strategic planning of realization of the chosen strategy; ecological monitoring, audit and control of strategies of implementation of the ecological policy; evaluation of the effectiveness of the chosen strategy of the ecological policy.